(3cJGH ef GdeDdaGJ GdOQRjIs
(3ChdgG (B:s
(3Chd OQLI JSdje GdLSe gh Cf GdGfSGf jSJYed LhGQMg GdSHYI ajeG NdbgG Gddg dg hgj GddSGf hGdYjf hGdCPf hGdjO hGdQLd hGdHWf hGdaQL hgPg GdLhGQM gi GdCQcGf GdJi CTGQ EdjgG s
(3BNQgG (B:s
(3adeG QBfi QHi Ydi Jdc GdMGd SeY fOGFi hCLGH OYGFi hQMe VYai hef TcQ aEfeG jTcQ dfaSg hef caQ aEf QHi Zfi cQje s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds